Epstein-Barr Virus Regulates STAT1 through Latent Membrane Protein 1 - Richardson, Ciarán (American Society for Microbiology, 2003)
This study shows a mechanism for the increase of signal transducer and activator of transcription 1 (STAT1) in Epstein-Barr virus-immortalized cells. Latent membrane protein 1 (LMP-1) expression was sufficient to induce STAT1 expression, DNA binding, and transcriptional activity. LMP-1-expressing cells can induce an increase in STAT1 expression in LMP-negative cells in the same culture, suggesting an indirect regulation of STAT1 expression. The increase in STAT1 expression is mediated by the C-terminal activating region 1 (CTAR-1) and/or CTAR-2 domains of LMP-1 and is inhibited by mutant IκB, demonstrating a role for NFκB in LMP-1-mediated STAT1 expression.